2021
DOI: 10.3390/cancers13225860
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Rearrangements and Altered Nuclear Organization: Recent Mechanistic Models in Cancer

Abstract: The last decade has seen significant progress in understanding how the genome is organized spatially within interphase nuclei. Recent analyses have confirmed earlier molecular cytogenetic studies on chromosome positioning within interphase nuclei and provided new information about the topologically associated domains (TADs). Examining the nuances of how genomes are organized within interphase nuclei will provide information fundamental to understanding gene regulation and expression in health and disease. Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…To assess the effect of B-type lamin degradation on chromosome-specific loci in live HCT116 LMN(B1&B2)−AID cells, we labeled genomic regions on chromosomes 3 and 19 using CRISPR-Sirius [55]. Chromosomes 3 and 19 were chosen to represent chromosomes that are localized relatively near the nuclear periphery and the nuclear interior, respectively [55][56][57][58][59][60]. Specifically, we chose one intronic gene region on Chromosome 3 (XXYLT1) containing ~ 333 endogenous tandem repeats, and one intronic gene region on Chromosome 19 (TCF3) containing ~ 36 endogenous tandem repeats as a reference to the nuclear interior.…”
Section: B-type Lamin Degradation Shifts the Preferential Localizatio...mentioning
confidence: 99%
“…To assess the effect of B-type lamin degradation on chromosome-specific loci in live HCT116 LMN(B1&B2)−AID cells, we labeled genomic regions on chromosomes 3 and 19 using CRISPR-Sirius [55]. Chromosomes 3 and 19 were chosen to represent chromosomes that are localized relatively near the nuclear periphery and the nuclear interior, respectively [55][56][57][58][59][60]. Specifically, we chose one intronic gene region on Chromosome 3 (XXYLT1) containing ~ 333 endogenous tandem repeats, and one intronic gene region on Chromosome 19 (TCF3) containing ~ 36 endogenous tandem repeats as a reference to the nuclear interior.…”
Section: B-type Lamin Degradation Shifts the Preferential Localizatio...mentioning
confidence: 99%
“…In the nuclei of healthy lymphocytes, MNX1 is localised at the periphery, and ETV6 is normally localised in the nuclear interior, therefore the repositioning of MNX1 into a transcriptionally active (internal) region due to the t(7;12) has been suggested to trigger its expression. Nuclear genome re-organisation due to the chromosomal abnormalities has been shown to affect gene regulation [ 67 , 68 ]; however, it remains unclear whether MNX1 ectopic expression is a cause or an effect of the nuclear reorganisation. Interestingly, previous nuclear localisation analysis also showed that MNX1 becomes transcriptionally active during neuronal differentiation of the neuroblastoma SK-N-BE cell line, and this activity is correlated with its relocation towards the nuclear interior [ 61 ].…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…In tumor tissues, it is well-known that chromosomal rearrangements can drive tumor growth [41,42]. Therefore, the fusions observed in medulloblastoma may result from such events.…”
Section: Discussionmentioning
confidence: 99%